Policing Schools: Examining the Impact of Place Management Activities on School Violence - Swartz, Kristin (American journal of criminal justice, 2016)
The present study examines whether the presence of school resource officers (SROs) and their level of involvement in place management activities are associated with higher or lower rates of school-based serious violence. This study uses data from the 2010 School Survey on Crime and Safety (SSOCS) conducted by National Center for Educational Statistics. Propensity score matching is used to create a quasi-experimental design and isolate the influence of SROs and their level of involvement in place management activities on school-based serious violence. The analysis reveals that schools with a school resource officer are associated with higher rates of reported serious violence and those schools with SROs that participate in more place manager duties are also associated with higher rates of reported serious violence. These findings do not support the notion that SROs are acting as effective place managers and through this place management, reducing reported serious violence. Rather, it appears that the presences of a SRO and their execution of place manager duties is associated with an increase in the reporting of serious violence. Policy implications and limitations of the current research are also discussed.